Retrospective evaluation of patients with diagnosis of atypical hemolytic uremic syndrome: Single center experience (Annals of Medical Research, 2022)
Aim: To evaluate the demographic, clinical, laboratory findings, genetic results and final status of patients followed-up with the diagnosis of atypical hemolytic uremic syndrome (aHUS)Materials and Methods: Patients who were diagnosed and followed up in our pediatric nephrology center between January 2013 and June 2021 were included in the study retrospectively. Demographic data, history, age at diagnosis, physical examination, laboratory tests, organ involvement, genetic results, treatments, kidney replacement therapies, follow-up and final status were evaluated.Results: A total of 14 patients, 9 girls (64.3%) and 5 boys (35.7%) were included in our study over a period of 8 years. The mean age at presentation was 66.7±54.1 months (5.5±4.5 years) and the follow-up period in our center was 50.7±37.1 months.  Recurrence was detected in 4 patients (28.6%) 18.5±20.4 months after diagnosis. In six of our patients (42.8%) neurological involvement was detected; 5 (35.7%) had hypertensive features and 1 (7.1%) had disease involvement. MCP (CD46) mutation was detected in 4 patients (28.6%), CFH mutation in 3 patients (21.4%), and CFHR1-CFHR3 mutation in 3 patients (21.4%). While a total of 4 patients (28.6%) died in our center, 10 patients (71.4%) are still being followed up and treated. From these patients one is followed up with fresh frozen plasma therapy and the rest with eculizumab therapy.Conclusion: Eculizumab is found to be an effective therapy for patients with aHUS who did not respond to plasmaphresis and/or plasma treatment. We think that eculizumab treatment may be the first choice considering with detailed genetic analysis (including antifactor H antibody) in the light of future multicenter studies with larger of patients.
Keywords: Atypical hemolytic uremic syndrome; Childhood; Cytogenetic analysis; Follow-up